EXPLORATORY PRACTICE AND ITS POTENTIAL FOR PEDAGOGY AND RESEARCH - Nicholas Musty (PUPIL: International Journal of Teaching, Education and Learning, 2026)
Exploratory Practice (EP) is a methodology of practitioner research which involves key stakeholders, often teaching faculty and students, in creating puzzles, an equivalent to the research question, which they go on to solve collaboratively without deference to a professional researcher. As a result, learners gain valuable insights to the entire research process and a sense of autonomy, while their heightened engagement encourages more considered outcomes. As part of his doctoral studies, the presenter is involved in a programme of EP with university students of English in Japan. This involves a senior team of students in carrying out research on the theme of emotions in the language classroom, determining an approach to learning more about this phenomenon through research on the wider student population. This presentation will focus on EP as a methodology, drawing on previous studies which extol its benefits to support the learnings gained through this project so far. The presenter will demonstrate the vast potential for combining teaching and research through EP. In addition, suggestions will be made regarding how to utilise EP in a way that will lead to the upscaling of institutions’ potential for research and the upskilling of both instructors and the wider student body.